E-cigarettes: no smoke without fire?. (1st June 2020) - Daniels, N.; Cosma, C.; Llewellyn, A.; Banks, D.; Morris, H.; Copeland, J.; Djarlijeva, E.
Abstract: Smoking was one of the biggest preventable killers of the 20 th century, and it continues to cause the death of millions across the globe. The rapid growth of the e-cigarette market in the last 10 years and the claims that it is a safer form of smoking, and can help with smoking cessation, have led to questions being raised on their possible impact to society, the health of the population and the insurance industry. Recent media attention around the possible health implications of e-cigarette use has also ensured that this topic remains in the public eye. The e-cigarette working party was initiated by the Institute and Faculty of Actuaries' Health and Care Research Sub-Committee in July 2016, with the primary objective of understanding the impact of e-cigarettes on life and health insurance. In this paper, we have looked at all areas of e-cigarette usage and how it relates to insurance in the UK market. In particular, we have covered the potential risks and benefits of switching to e-cigarettes, the results of studies that have been published, the potential impact on underwriting and claims processes and the potential impact on pricing (based on what modelling is possible with the data available). Research in this area is still in its infancy and data are not yet mature, which makes predicting the long-term impact of e-cigarette smoking extremely challenging, for example, there are no studies that directly measure the mortality or morbidity impact of long-term e-cigarette use and so we have had to consider studies that consider more immediate health impacts or look more simply at the constituents of the output of an e-cigarette and compare them to that of a cigarette. The data issue is further compounded by the findings of studies and the advice of national health authorities often being conflicting. For example, while National Health Service England has publicly stated that it supports the growth of e-cigarette usage as an aid to reduce traditional smoking behaviour, the US Food and Drug Administration has been much more vocal in highlighting the perceived dangers of this new form of smoking. Users' behaviour also adds complexity, as dual use (using both e-cigarettes and cigarettes) is seen in a high percentage of users and relapse rates back to cigarette smoking are currently unknown. Having talked to a number of experts in the field, we have discovered that there is certainly not a common view on risk. We have heard from experts who have significant concerns but also to experts who do believe that e-cigarettes are far safer than tobacco. We have purposefully considered conflicting evidence and have consulted with various parties so we can present differing points of view, thereby ensuring a balanced, unbiased and fair picture of our findings is presented. The evidence we have reviewed does suggest that e-cigarettes are a safer alternative to traditional smoking, but not as safe as non-smoking. There are no large, peer-reviewed, long-term studies yet available to understand the true impact of a switch to e-cigarette use, so currently we are unable to say where on the risk spectrum between cigarette smoking and life-time non-smoking it lies. We do not yet understand if the benefits seen in the studies completed so far will reduce the risk in the long term or whether other health risks will come to light following more prolonged use and study. This, coupled with concerns with the high proportion of dual use of cigarettes and e-cigarettes, relapse rates and the recent growth in medical problems linked with e-cigarette use, means that we need to wait for experience to emerge fully before firm conclusions can be drawn. Although we have presented a view, it is vitally important that our industry continues to monitor developments in this area and fully considers what next steps and future actions may be required to ensure our position reflects the potential benefits and risks that e-cigarette use may bring. We feel that the time is right for a body such as the IFoA to analyse the feasibility of collecting the necessary data through the Continuous Mortality Investigation that would allow us to better analyse the experience that is emerging.